Accessible continued professional development for maternal mental health - Sally Field; Zulfa Abrahams; David L. Woods; Roseanne Turner; Michael N. Onah; Doreen K. Kaura; Simone Honikman (AOSIS, 2019)
Background: Changing global health and development trends have resulted in a need for continued professional development (CPD) within the health and development sectors. In low-resource settings, where the need for training and CPD may be highest, there are significant challenges for disseminating information and skills. There is a need to improve mental health literacy and reduce levels of stigma about maternal mental illness. The Bettercare series of distance learning books provides a peer-based format for CPD. We aimed to evaluate the Bettercare Maternal Mental Health book as a format for CPD. Aim: The aim of this study was to determine whether the Bettercare Maternal Mental Health book significantly improves knowledge and decreases stigma around mental health for care providers from the health and social development sectors. Setting: One hundred and forty-one participants (social workers, nursing students and health professionals) were provided with the Bettercare Maternal Mental Health book to study. Methods: Before and after studying the book, the same multiple-choice knowledge test and the Mental Illness Clinicians' Attitude Scale were used to assess cognitive knowledge and mental health stigma, respectively. Results: Participants' knowledge showed a statistically significant (p < 0.001) improvement between the pre- and post-test results, for all six chapters of the book. However, participants' attitudes towards mental illness did not show a statistically significant change between the pre- and post-test results. Conclusion: We found that this method of learning elicited significant improvement in mental health knowledge for care providers. Continued professional development policy planners and curriculum developers may be interested in these findings.